Fermented Astragalus and its metabolites regulate inflammatory status and gut microbiota to repair intestinal barrier damage in dextran sulfate sodium-induced ulcerative colitis - Li, Junxiang; Ma, Yingchun; Li, Xiaofeng; Wang, Yafei; Huo, Zeqi; Lin, Yang; Li, Jiaru; Yang, Hui; Zhang, Zhiming; Yang, Pingrong; Zhang, Chunjiang (Frontiers in Nutrition, 2022)
Fermentation represents an efficient biotechnological approach to increase the nutritional and functional potential of traditional Chinese medicine. In this study, Lactobacillus plantarum was used to ferment traditional Chinese medicine Astragalus, the differential metabolites in the fermented Astragalus (FA) were identified by UPLC-Q-Exactive-MS, and the ameliorating effect of FA on dextran sulfate sodium (DSS)-induced colitis in mice were further explored. The results showed that 11 differential metabolites such as raffinose, progesterone and uridine were identified in FA, which may help improve the ability of FA to alleviate colitis. Prophylactic FA supplementation effectively improved DAI score, colon length and histopathological lesion in DSS-treated mice. The abnormal activation of the intestinal immune barrier in mice was controlled after FA supplementation, the contents of MPO and IgE were reduced and the contents of IgA were increased. The intestinal pro-inflammatory factors TNF-α, IL-1β, IL-6, and IL-17 were down-regulated and the anti-inflammatory factors IL-10 and TGF-β were up-regulated, suggesting that FA can intervene in inflammatory status by regulating the balance of Th1/Th2/Th17/Treg related cytokines. In addition, FA supplementation modified the structure of the intestinal microbiota and enriched the abundance of Akkermansia and Alistipes, which were positively associated with the production of short-chain fatty acids. These microbes and their metabolites induced by FA also be involved in maintaining the intestinal mucosal barrier integrity by affecting mucosal immunity. We observed that intestinal tight junction protein and mucous secreting protein ZO-1, occludin, and MUC2 genes expression were more pronounced in mice supplemented with FA compared to unfermented Astragalus, along with modulation of intestinal epithelial cells apoptosis, verifying the intestinal mucosal barrier repaired by FA. This study is the first to suggest that FA as a potential modulator can more effectively regulate the inflammatory status and gut microbiota to repair the intestinal barrier damage caused by colitis.